2020
DOI: 10.3390/pr8101262
|View full text |Cite
|
Sign up to set email alerts
|

Green Dairy Plant: Process Simulation and Economic Analysis of Biogas Use in Milk Drying

Abstract: A project of a new milk drying unit processing 4800 kg/h of fresh milk into milk powder with expected steam consumption of 1000 kg/h (equivalent to ca. 2.6 GJ/h) was assessed. In this paper, investment profitability of this project was analyzed combining mathematical modeling, market analysis, and parametric sensitivity study. Aspen Plus was used as the simulation environment to determine values of key process variables—major streams, mass flows, and energy consumption. Co-digestion of cattle manure in an adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…For example, Quintero et al (2013) used Excel and MATLAB subroutines to reproduce detoxification and sugar fermentation reactions; Madoumier et al (2017) applied generic built‐in unit operation coupled with short‐cut models to represent pre‐heaters and pasteurizers with pre‐established heat exchangers. In Janošovský et al (2020), the burner was simulated as a stoichiometric reactor with defined 100% conversion of combustible components, the furnace as a shell‐and‐tube heat exchanger, and the feed water preheater as a mixer. All these works are detailed and listed in Table 2, among other relevant cases of study in the food process field, found in literature, in line with this review.…”
Section: Commercial Simulation Softwarementioning
confidence: 99%
See 3 more Smart Citations
“…For example, Quintero et al (2013) used Excel and MATLAB subroutines to reproduce detoxification and sugar fermentation reactions; Madoumier et al (2017) applied generic built‐in unit operation coupled with short‐cut models to represent pre‐heaters and pasteurizers with pre‐established heat exchangers. In Janošovský et al (2020), the burner was simulated as a stoichiometric reactor with defined 100% conversion of combustible components, the furnace as a shell‐and‐tube heat exchanger, and the feed water preheater as a mixer. All these works are detailed and listed in Table 2, among other relevant cases of study in the food process field, found in literature, in line with this review.…”
Section: Commercial Simulation Softwarementioning
confidence: 99%
“…With the main objective of analyzing energy consumption and costs, Janošovský et al (2020) simulated the whole production line to obtain powder milk using Aspen Plus. Milk was simulated as an aqueous solution of six chemicals representing fat (palmitic and oleic acid), carbohydrates (lactose), minerals (calcium and potassium), and proteins (proline).…”
Section: Cases Of Study In the Food Process Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Eliminating these contaminants is of great relevance and this is particularly true for the removal of H 2 S. This compound may cause serious corrosion problems and give rise to operability issues associated with its oxidation products. In the case of CO 2 , the importance of removing this compound is based on the quality standard of biogas and the type of valorization technology this gas will be destined to [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%